Caracterização genética e detecção de mecanismos de resistência de Neisseria meningitidis isoladas no Laboratório Central de Saúde Pública de Minas Gerais, 2017-2019 - Dhian Renato Almeida Camargo (2021)
The infection by Neisseria meningitidis is associated with high levels of morbidity and mortality in children and young adults worldwide. In Brazil, the meningococcal disease is endemic and 1037 confirmed cases had been reported in 2019. This study showed the genetic characterization and detection of antimicrobial resistance mechanisms in 35 strains of N. meningitidis isolated in the LACEN-MG between 2017 and 2019. The isolates were genetically characterized by multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). The antimicrobial sensitivity pattern was determined using Etest® and the resistance mechanism was analyzed by sequencing of the penA gene. The occurrence in female patients was 57.1%, and 28.6% of these patients were up to 14 years old. The majority of the isolates came from the health region of Belo Horizonte (11/35) and Uberlândia (11/35). The most frequent groups per type/subtype (group:type:subtype) were C:23:P1.14-6 (n=11), B:4.7: P1.19.15 (n=3), W:2a:P1.2 (n=2) and Y:4:nt (n=1). PFGE identified eight pulsotypes (A-H), while MLST identified 14 clones. The most prevalent clones were ST12020, ST11 and ST3780. The sequence types were grouped into eight clonal complexes (cc). The cc103 (48.6%), belonging to the PFGE pulsotype B, was the most frequent and associated with N. meningitidis group C phenotype [23:P1.14-6, nt:ST12020, ST3780, ST8730]. All strains were sensitive to ceftriaxone, ciprofloxacin and rifampicin, while one strain was resistant to penicillin (MIC = 0.5 μg mL-1) and 20 showed intermediate sensitivity to penicillin (penI) (MIC between 0.09 and 0.25 μg mL-1). From the strains with resistance profile, five alleles of the penA gene were identified and the penA14 allele was the most prevalent. In general, the identified penA alleles had polymorphisms associated with the penI phenotype. Our study showed that there was a predominance of the invasive lineage NmC:23:P1.14-6:ST12020:cc103:penA14 with reduced sensitivity to penicillin, and that resistance to ceftriaxone, ciprofloxacin and rifampicin was not detected.